Analisis Kinerja Sistem Pemotongan Dan Penjahitan Karung Woven Otomatis Tipe Qf-950 Di PT. Plastindo Pack Printing - Adji, Desta (Fakultas Teknik Universitas Lampung, 2025)
This research was conducted to examine the performance of the automatic woven bag cutting and sewing system type QF-950 implemented in the production process at PT. Plastindo Pack Printing. The main focus of the study includes process speed, the accuracy of the output, machine operation stability, and the system’s ability to support sustainable productivity. The evaluation was carried out through direct observation of the machine’s performance during production and by comparing it with the manual work method previously used as the primary approach.The analysis results indicate that this automation technology is able to simplify workflow, reduce operator fatigue, and minimize the likelihood of product defects in both size and seam quality. In addition, the automatic system provides improvements in time and material efficiency because the process runs more precisely and does not require repeated adjustments.Overall, the use of the QF-950 machine is considered effective in helping the company achieve uniform, fast, and industry-standard production results. Thus, the implementation of automation is considered feasible to be further developed as an effort to enhance production competitiveness.